2020
DOI: 10.1002/jcla.23542
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a predictive model for the prognosis in aneurysmal subarachnoid hemorrhage

Abstract: Aneurysmal subarachnoid hemorrhage (aSAH) is an acute cerebrovascular disease that seriously damages the central nervous system and simultaneously exerts pathophysiological effects on multiple organs of the body, with high mortality and morbidity. 1,2 Approximately onethird of the survivors suffer from severe disability and functional dependency. 3 Rebleeding is a major early complication of aSAH with the incidence of 6%-23%, which most occurs within 72 hours of onset. 4,5 Previous studies reported that the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…However, the NLR in patients with an unfavorable prognosis was higher than that in patients with a favorable prognosis in the training cohort ( p = 0.005). Our study identified NLR on admission as an independent risk factor for unfavorable prognosis, similar to previous findings ( 4 , 7 , 33 , 34 ). Lai et al reported that a high NLR on admission could increase the risk of poor prognosis 3 months postoperatively.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, the NLR in patients with an unfavorable prognosis was higher than that in patients with a favorable prognosis in the training cohort ( p = 0.005). Our study identified NLR on admission as an independent risk factor for unfavorable prognosis, similar to previous findings ( 4 , 7 , 33 , 34 ). Lai et al reported that a high NLR on admission could increase the risk of poor prognosis 3 months postoperatively.…”
Section: Discussionsupporting
confidence: 92%
“…These factors were selected using univariate and multivariate logistic analyses. Lai et al conducted a predicting model for aSAH prognosis, which included the GCS score, surgical clipping, and NLR ( 7 ). These independent prognostic variables were also selected by multivariate logistic regression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the included studies are summarized in Table 1. We included 10 studies consisting of 4,140 patients in this meta-analysis (10,(20)(21)(22)(23)(24)(25)(26)(27)(28). Nine studies investigated the association between NLR and poor functional outcome (10,(20)(21)(22)(23)(24)(26)(27)(28), and six studies investigated the association between NLR and DCI (20,22,(25)(26)(27).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…We included 10 studies consisting of 4,140 patients in this meta-analysis (10,(20)(21)(22)(23)(24)(25)(26)(27)(28). Nine studies investigated the association between NLR and poor functional outcome (10,(20)(21)(22)(23)(24)(26)(27)(28), and six studies investigated the association between NLR and DCI (20,22,(25)(26)(27). Most of the studies were retrospective observational studies, and only three studies were prospective studies.…”
Section: Study Characteristicsmentioning
confidence: 99%